Phthalate Esters in Different Types of Cosmetic Products: A Five-Year Quality Control Survey - Natalia Aldegunde-Louzao; Manuel Lolo-Aira; Carlos Herrero-Latorre (Molecules, 2024)
Phthalate esters are commonly included in the formulations of cosmetics and related products in order to retain fragrance, enhance flexibility (i.e., by acting as plasticizers), facilitate the dissolution and dispersion of other ingredients, and improve the overall texture and sensory experience of the products. This study aimed to assess the presence and concentrations of phthalates in cosmetics by analyzing a comprehensive set of samples collected over a period of five years (2016–2020). The concentrations of nine different phthalate esters (BBP, DEHP, DNOP, DPP, DBP, DIPP, DMEP, DMP and PIPP) in 1110 cosmetics samples from France and Spain were determined by gas chromatography–mass spectrometry. The samples were included in five categories: soaps and shampoos; hand and body creams; lip gloss and lipsticks; nail polish; and facial makeup and skincare products. Some of the samples (4.86%) contained at least one phthalate at concentrations above the threshold limit (1 µg mL−1). Variable concentrations of different phthalates were determined in the 54 positive samples identified. DEHP was the most frequently detected phthalate, followed by DBP. The findings revealed different profiles according to the different categories of cosmetics and the phthalates detected in each. The results were critically compared with those obtained in various previous studies.